Consider the equation: 2x - 6 = 5 - 3y.
It is an equation with two variables, x and y, which can be transformed into a simpler equivalent equation. Watch:
2x + 3y = 5 + 6
2x + 3y = 11 ==> Equation of the first degree in the form ax + by = ç.We call it 1st degree equation with two variables, x and y, every equation that can be reproduced in the form ax + by = ç, being The and B non-zero numbers simultaneously.
In the equation ax + by = ç, we call it:
| x and y - variables or unknown |
The - coefficient of x
| B - coefficient of y |
ç - independent term
|x + y = 30|
2x + 3y = 15
x - 4y = 10
|-3x - 7y = -48|
2x- 3y = 0
x - y = 8